The Protective Effects of Lupine (Lupinus albus) Fruit Extract Against to Destructive Effects of Hyperglycemia in Type I Diabetic Rats - Aydin, Sevinc; Kaya, Tubay; Erman, Orhan; Yilmaz, Okkes (Bentham Science Publ Ltd, 2021)
Background: Lupinus albus is a member of the Fabaceae family. As a natural or cultivat-ed plant, Lupinus albus is distributed in Europe, the Balkans and Turkey, especially in Marmara and Aegean regions. The lupine is a nutritious and protective plant against diabetes. Objective: In the present study, the effects of Lupinus albus fruits on malondialdehyde (MDA), re-duced glutathione (GSH), total protein, ADEK vitamins, and cholesterol values, which are the indi-cators of oxidative damage and antioxidant defense. In this regard, muscle, liver, renal, and brain tissues of STZ-induced type I diabetes rats were studied. Methods: The analyzes of ADEK vitamins and cholesterol levels in tissues were performed via Shimadzu HPLC device. The lipid peroxidation levels were measured at 532 nm in spectrophotome-ter. Determination of GSH was read at 412 nm against blank, and for the total protein levels Lowry method was applied. Results: According to the results obtained, it was determined that among the rats with induced type I diabetes, the group applied lupine fruit extract was found to have increased GSH level and de-creased MDA levels in all the tissues. The protein values were increased in liver tissues but de-creased in the other tissues. The level of vitamins was significantly increased in almost all the tis-sues in the diabetic group. Conclusion: In the present study, it was shown that the lupine reduced the devastating effects of type I diabetes by decreasing the fasting blood glucose and lipid peroxidation values and increasing the glutathione level in comparison to the diabetic group.
Keywords: Diabetes; Lupinus albus; vitamin; cholesterol; MDA; GSH